Implementation Of Regional Financial Management Policy In Supporting The Vision And Mission Of The Regent Of Indramayu - Ramdhani, Harri; Fathul Amri, Moh; erna; Kurniawan, Zuki (LPPM STIA Lancang Kuning Dumai, 2026)
This study examines the implementation of regional financial management policy in supporting the vision and mission of the Regent of Indramayu. The analysis focuses on the alignment between the General Budget Policies and Provisional Budget Ceilings and Priorities (KUA–PPAS) and the Regional Medium-Term Development Plan (RPJMD) and Annual Government Work Plan (RKPD), the effectiveness of the Local Government Budget (APBD) formulation process, the contribution of financial administration and reporting to correcting expenditure classification errors, and the obstacles encountered during implementation. Using a descriptive qualitative approach, data were collected through in-depth interviews and document analysis involving ten key informants from Bappeda, the Regional Financial and Asset Management Office (BPKAD), and related local government units. Data were analyzed using Miles and Huberman’s qualitative analysis model. The findings reveal that the synchronization between KUA–PPAS and RPJMD–RKPD is generally adequate, although several programs during the first years of implementation were not fully aligned. The APBD preparation process effectively supports the Regent’s priority programs. Financial administration and reporting significantly contribute to correcting misclassified expenditure accounts through systematic reclassification. The main constraints include regulatory inconsistencies, limited human resource capacity, weak cross-unit coordination, and suboptimal use of information systems. Strengthening planning–budgeting integration, enhancing human resource competency, and maximizing digital-based financial systems are crucial for improving policy implementation.